Sex Differences in Ischemic Heart Disease: Advances, Obstacles, and Next Steps. Issue 2 (February 2018) - Aggarwal, Niti R.; Patel, Hena N.; Mehta, Laxmi S.; Sanghani, Rupa M.; Lundberg, Gina P.; Lewis, Sandra J.; Mendelson, Marla A.; Wood, Malissa J.; Volgman, Annabelle S.; Mieres, Jennifer H.
Abstract : Evolving knowledge of sex-specific presentations, improved recognition of conventional and novel risk factors, and expanded understanding of the sex-specific pathophysiology of ischemic heart disease have resulted in improved clinical outcomes in women. Yet, ischemic heart disease continues to be the leading cause of morbidity and mortality in women in the United States. The important publication by the Institute of Medicine titled "Women's Health Research—Progress, Pitfalls, and Promise, " highlights the persistent disparities in cardiovascular disease burden among subgroups of women, particularly women who are socially disadvantaged because of race, ethnicity, income level, and educational attainment. These important health disparities reflect underrepresentation of women in research, with the resultant unfavorable impact on diagnosis, prevention, and treatment strategies in women at risk for cardiovascular disease. Causes of disparities are multifactorial and related to differences in risk factor prevalence, access to care, use of evidence-based guidelines, and social and environmental factors. Lack of awareness in both the public and medical community, as well as existing knowledge gap regarding sex-specific differences in presentation, risk factors, pathophysiology, and response to treatment for ischemic heart disease, further contribute to outcome disparities. There is a critical need for implementation of sex- and gender-specific strategies to improve cardiovascular outcomes. This review is tailored to meet the needs of a busy clinician and summarizes the contemporary trends, characterizes current sex-specific outcome disparities, delineates challenges, and proposes transformative solutions for improvement of the full spectrum of ischemic heart disease clinical care and research in women.